A 3D metal–organic framework with dual-aerial-octahedral trinucleate building units: synthesis, structure and fluorescence sensing properties. (13th August 2018) - Zhao, Yan-Ning; Zhang, Shu-Ran; Wang, Wei; Xu, Yan-Hong; Che, Guang-Bo
Abstract : JLNU-2 can be used to detect nitrobenzene with high selectivity, sensitivity, anti-interference ability and recyclability through tracing the fluorescence quenching behaviour. Abstract : A six-coordinated 3D metal–organic framework (MOF), [ZnK(tatab)(CH3 OH)]·3DMF·4.5CH3 OH (JLNU-2, JLNU = Jilin Normal University, H3 tatab = 4, 4′, 4′′-((1, 3, 5-triazine-2, 4, 6-triyl)tris(azanediyl)) tribenzoic acid, DMF = N, N -dimethylformamide), has been purposefully constructed by combining the N-donor ligand H3 tatab with aromatic π rings and d 10 configuration metal Zn(ii ) nitrate under solvothermal conditions. The crystal structure reveals thatJLNU-2 consists of a dual-aerial-octahedral trinuclear potassium cluster and zinc building units with N–H⋯O hydrogen bonding, which are further bridged by N-donor multicarboxylate ligands to produce a (3, 6)-connected topological net in an interesting hot-wheel state. The special hydrogen bonding strongly promotes the molecular luminescence sensitivity. The experimental results show thatJLNU-2 exhibits outstanding fluorescence quenching properties via an electron transfer mechanism from the electron-rich framework to the electron-withdrawing group of nitrobenzene. The fluorescence was quenched completely in the presence of 130 ppm of nitrobenzene. After 8 cycles, the quenching efficiency was maintained at 88.9%. As a result, the MOF material is extremely well qualified to be a fluorescence sensor for the detection of nitrobenzene owing to its supreme selectivity, sensitivity, anti-interference ability and recyclability.